Facile approach to N,O,S-heteropentacycles via condensation of sterically crowded 3H-phenoxazin-3-one with ortho-substituted anilines - Ivakhnenko, Eugeny; Malay, Vasily; Knyazev, Pavel; Merezhko, Nikita; Makarova, Nadezhda; Demidov, Oleg; Borodkin, Gennady; Starikov, Andrey; Minkin, Vladimir (Beilstein Journal of Organic Chemistry, 2024)
A convenient method for the synthesis of a series of 2-(arylamino)-3H-phenoxazin-3-ones based on the nucleophilic substitution reaction between sterically crowded 3H-phenoxazin-3-one and arylamines performed by short-term heating of the melted reactants at 220–250 °C is described, and the compounds were characterized by means of single-crystal X-ray crystallography, NMR, UV–vis, and IR spectroscopy, as well as cyclic voltammetry. The reaction with o-amino-, o-hydroxy-, and o-mercapto-substituted arylamines widened the scope and provided an access to derivatives of N,O- and N,S-heteropentacyclic quinoxalinophenoxazine, triphenodioxazine and oxazinophenothiazine systems.
Keywords: 3H-phenoxazin-3-one; fluorescence; molecular structure; pentacyclic heterocycles; synthesis